2000
DOI: 10.1046/j.1365-2141.2000.01793.x
|View full text |Cite
|
Sign up to set email alerts
|

P‐glycoprotein and multidrug resistance‐associated protein, but not lung resistance protein, lower the intracellular daunorubicin accumulation in acute myeloid leukaemic cells

Abstract: Summary. The in vitro intracellular daunorubicin accumulation (IDA) of blast cells from 69 patients with newly diagnosed acute myeloid leukaemia (AML) was correlated with the expression and functional activity of the multidrug resistance (MDR) proteins, P-glycoprotein (Pgp), multidrug resistance-associated protein (MRP) and lung-resistance protein (LRP). An inverse and signi®cant association was found between IDA and Pgp-related ef¯ux activity (r À0´31, P 0´01) and also MRP (r À0´25, P 0´04) but not with LRP (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…Izquierdo et al [11 ]examined expression of P-gp, MRP1, and LRP in 58 human cancer cell lines and found co-expression of two or three MDR proteins in 64% of the lines, which was associated with high levels of drug resistance. Borg et al [38]observed that co-expression of MDR proteins has an additive effect in the lowering of drug accumulation levels in leukemic cell lines. Co-expression of MDR proteins has been reported in multiple myeloma [39], AML [13], and soft tissue sarcoma [40].…”
Section: Discussionmentioning
confidence: 99%
“…Izquierdo et al [11 ]examined expression of P-gp, MRP1, and LRP in 58 human cancer cell lines and found co-expression of two or three MDR proteins in 64% of the lines, which was associated with high levels of drug resistance. Borg et al [38]observed that co-expression of MDR proteins has an additive effect in the lowering of drug accumulation levels in leukemic cell lines. Co-expression of MDR proteins has been reported in multiple myeloma [39], AML [13], and soft tissue sarcoma [40].…”
Section: Discussionmentioning
confidence: 99%
“…MRP, as well as P-gp, has been reported to be over-expressed on some leukemia cells and associated with lower intracellular drug accumulation in AML. 33 However, the impact of MRP on clinical outcomes in AML remains to be proven. Our data suggest that MRP is not associated with CMA-676 resistance in AML, but further investigations are required to clarify this association.…”
Section: Discussionmentioning
confidence: 99%
“…Expression and function of Pgp in de novo AML patients has been shown to be an independent adverse prognostic factor for response and survival. [20][21][22][23][24][25][26] Furthermore, in some studies higher Pgp expression was found in refractory and relapsed AML. 22,24,27 The use of rhodamine123 as Pgp probe, combined with PSC833 as Pgp inhibitor in an accumulation assay represents a sensitive and reproducible functional assay in AML both in efflux 28 and accumulation 29,30 assay and is also applicable for frozen/thawed samples.…”
Section: Introductionmentioning
confidence: 99%
“…31 Apart from Pgp, MRP1 (further referred to as MRP) might contribute to the multidrug resistance (MDR) phenotype in AML. 24,25,[32][33][34][35][36] It has been shown that among others the combination of calcein-AM and probenecid can be used to detect MRP function. 37,38 To investigate the role of Pgp and MRP in drug resistance in AML, the most informative approach would be to functionally characterize MRD cells at different stages of disease of the patient.…”
Section: Introductionmentioning
confidence: 99%